Lead free organic-inorganic perovskites simulation for low toxic solar cell applications - Hima Abdelkader; Lakhdar Nacereddine; Benhaoua Boubaker; Kemerchou Imad; Rogti Fatiha (University of Eloued, 2019)
CH3NH3PbI3 Perovskite materials applied in organic-inorganic solar cell applications suffer from Pb toxicity. Recent researches aim to find out other alternates free lead materials. In this paper, numerical simulations of free lead perovskite CH3NH3SnI3 have been studied and results have been presented in order to show their performances in comparison of those of CH3NH3PbI3 using SCAPS software. The obtained results show that CH3NH3SnI3 has better performances compared to CH3NH3PbI3
Intervention
Keywords: CH3NH3PbI3; CH3NH3SnI3; IV; power conversion efficiency; lead free perovskite